Dynaforce International Pte Ltd : service innovation through public-private partnerships - Lim, June Mo Fang (2013)
Jimmie Lee founded Dynaforce International Private Limited in 1989, distributing fitness equipment to the Singapore market. Since then it has grown into a diversified company offering high-end fitness products, gym design services and wellness education.